Sex differences in national rates of repair of emergency abdominal aortic aneurysm. Issue 1 (5th November 2018) - Aber, A; Tong, T S; Chilcott, J; Thokala, P; Maheswaran, R; Thomas, S M; Nawaz, S; Walters, S; Michaels, J
Abstract: Background: The aim of this study was to assess the sex differences in both the rate and type of repair for emergency abdominal aortic aneurysm (AAA) in England. Methods: Hospital Episode Statistics (HES) data sets from April 2002 to February 2015 were obtained. Clinical and administrative codes were used to identify patients who underwent primary emergency definitive repair of ruptured or intact AAA, and patients with a diagnosis of AAA who died in hospital without repair. These three groups included all patients with a primary AAA who presented as an emergency. Sex differences between repair rates and type of surgery (endovascular aneurysm repair (EVAR) versus open repair) over time were examined. Results: In total, 15 717 patients (83·3 per cent men) received emergency surgical intervention for ruptured AAA and 10 276 (81·2 per cent men) for intact AAA; 12 767 (62·0 per cent men) died in hospital without attempted repair. The unadjusted odds ratio for no repair in women versus men was 2·88 (95 per cent c.i. 2·75 to 3·02). Women undergoing repair of ruptured AAA were older and had a higher in-hospital mortality rate (50·0 versus 41·0 per cent for open repair; 30·9 versus 23·5 per cent for EVAR). After adjustment for age, deprivation and co-morbidities, the odds ratio for no repair in women versus men was 1·34 (1·28 to 1·40). The in-hospital mortality rate after emergency repair of an intact AAA was also higher among women. Conclusion: Women who present as an emergency with an AAA are less likely to undergo repair than men. Although some of this can be explained by differences in age and co-morbidities, the differences persist after case-mix adjustment. Abstract : Why worse for women?